Leading the Newly Merged High School: Exciting Opportunity or Overwhelming Challenge? - Lance E. Thurman; Donald G. Hackmann (Educational Considerations, 2015)
In the current economic times, school personnel are regularly challenged to reduce the costs of operating the nation’s school systems. School district consolidations often are proposed as a mechanism to realize fiscal savings for local communities; indeed, the number of U.S. school districts has declined dramatically over the past 70 years, decreasing from 117,108 in 1939-40 to 13,809 in 2008-2009.
Keywords: Literature; School District; Leadership; Learning; research; student learning; leadership; conversation; open dialogue; unified school culture